Doc at a Distance. - Rosen, J. (IEEE spectrum)
A team of scientists from the US Army's Telemedicine and Advanced Technology Research Center is working to develop a new generation of remotely-controlled surgical robots that would allow military doctors, stationed safely distant from the front line, to perform operations without once putting their hands on patients. Part of the High Altitude Platforms Mobile Robotics Telesurgery project, this endeavor aims to demonstrate the concept of remote robotic surgery in the field, using a rugged surgical robot and an airborne communications link. With medical vehicles equipped with such remote-controlled robots, surgical care can be provided to soldiers in a lot less time than it would take to evacuate them to the nearest base or hospital. The team hopes these robots could also be used to bring advanced medical care not just to soldiers but to people in remote locations lacking in specialized physicians. A prototype of these remote-controlled robots is undergoing field testing at an isolated site north of Simi Valley in southwestern California to evaluate how well it performs outside the controlled environment of an operating with less than ideal conditions